Influência do eletrólito de suporte no processo de eletrocoagulação: melhora na eficiência energética, geração de ferro e redução de tetraciclina - Valençola, William Vitor Rodrigues (2021)
The objective of the present work was to observe the influence of the supporting electrolyte in the electrocoagulation process, in search of the electrolyte that allows steady regimes of electrical conductivity, total electrical voltage, pH and iron insertion, in addition to observe his influence to remove tetracycline seeking an increase in energy efficiency for the treatment of this drug through the electrocoagulation technique. The experiments were carried out in a reactor with a useful volume of 1L, with 9 iron electrodes equidistant at 1.7 cm and an effective area of 0.0744 m². Firstly, electrocoagulation tests with different support electrolytes were carried out in order to observe his removal, in addition to the insertion of ferrous ions in the presence of each cation, and his influence on the electrical conductivity of the process. The supporting electrolytes chromium chloride, zinc chloride, calcium chloride and potassium chloride were taken. After choosing the best electrolyte from the energetic point of view, tests were performed using calcium chloride and zinc chloride as support electrolytes in the removal of tetracycline by electrocoagulation. Among the tested electrolytes, calcium chloride was determined as the ideal, as it provided the conditions for a steady state of electrical conductivity, electrical voltage, pH and iron insertion. After choosing the ideal support electrolyte, a Box-Behnken experimental design, with tetracycline removal as the dependent variable, was performed. With the results obtained by Box-Behnken planning, adaptations in the time-integrated performance index (TIPI) proposed by ROMANI et al. 2020 were carried and the TIPI index proposed in this work was calculated and inserted as a response variable for the Box-Behnken planning, in order to observe the conditions where the index could be higher. The EC technique combined with calcium chloride as the supporting electrolyte achieved removals greater than 98% of tetracycline for tests with higher electric current densities and longer times, however, the experimental design having the TIPI proposed as the dependent variable indicated as the best condition for the tests with longer times and lower current densities, reaching removals greater than 97% with a total cost 3.77 times lower than that presented by the best condition presented by the experimental removal planning.